2008
DOI: 10.1145/1352782.1352788
|View full text |Cite
|
Sign up to set email alerts
|

Queuing Network Modeling of Transcription Typing

Abstract: Transcription typing is one of the basic and common activities in human-machine interaction and 34 transcription typing phenomena have been discovered involving many aspects of human performance including interkey time, typing units and spans, typing errors, concurrent task performance, eye movements, and skill effects. Based on the queuing network theory of human performance [Liu 1996;1997] and current discoveries in cognitive and neural science, this article extends and applies the Queuing Network-Model Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 100 publications
2
66
0
Order By: Relevance
“…Theories of typing typically assume an important role for schematic representations in the control of keystroke execution (John, 1996;Rumelhart & Norman, 1982;Salthouse, 1986;Wu & Liu, 2008). Schemas refer to node-like summary representation coding the details of motor effectors movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theories of typing typically assume an important role for schematic representations in the control of keystroke execution (John, 1996;Rumelhart & Norman, 1982;Salthouse, 1986;Wu & Liu, 2008). Schemas refer to node-like summary representation coding the details of motor effectors movements.…”
Section: Discussionmentioning
confidence: 99%
“…In domains such as skilled typing, the focus of our current investigations, successful task performance relies on a series of specific, well-practiced movement patterns for keystroke execution (Rieger, 2004). Models of typing (John, 1996;Rumelhart & Norman, 1982;Salthouse, 1986;Wu & Liu, 2008) assume that reliable keystroke execution is controlled by stable schemas developed through years of practice. Our experiments test the notion that skilled typing could be controlled by episodic memory processes involved in coding the details of individual typing experiences.…”
mentioning
confidence: 99%
“…In other words, once the task procedures of each individual task are implemented in the model, the model will generate dual-task performance by letting the two streams of entities representing the two individual tasks in a dual task run through the model. With this modeling approach, we have successfully modeled a range of complex tasks, including driving (Liu et al, 2006;Wu & Liu, 2007a) and transcription typing (Wu & Liu, 2008). The PRP modeling work reported in this article is one of our modeling efforts along this direction, focusing on the most basic and fundamental aspect of multitask performance and using closed-form mathematical equations as the modeling method.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, years of practice are necessary to build up the requisite procedural knowledge, but that knowledge will not be explicitly available. In typewriting, the paradox of skill is resolved by proposing a hierarchical control system with two nested feedback loops: an inner loop that translates words into keystrokes and controls the movements of the fingers and hands, and an outer loop that connects to language generation and comprehension processes and provides the inner loop with a string of words to type (Crump & Logan, in press -a; Logan & Crump, 2009;Shaffer, 1975; see also John, 1996;Rumelhart & Norman, 1982;Salthouse, 1986;Wu & Liu, 2008). Logan and Crump (2009) suggested that the inner and outer loops are informationally encapsulated, so that the outer loop has no explicit knowledge of what the inner loop is doing.…”
mentioning
confidence: 99%